Molten Salt Synthesis, Polymorphism, and Microwave Dielectric Properties of Ba8NiTa6O24 Perovskite. Issue 8 (28th April 2015) - Gong, Meilu; Lu, Fengqi; Kuang, Xiaojun; Yu, Xiaodi; Wang, Quanchao; Li, Xiaohui; Fang, Liang
Abstract : Molten salt synthesis (MSS) of the eight‐layer hexagonal perovskite Ba8 NiTa6 O24 was performed using mixed KCl–NaCl salts in comparison with solid‐state synthesis (SSS). In the SSS, the hexagonal Ba8 NiTa6 O24 formed at 1300°C via a reaction between cubic Ba3 NiTa2 O9 and hexagonal Ba5 Ta4 O15 . While the MSS did not lower the synthesis temperature of the hexagonal Ba8 NiTa6 O24 but stabilized an unusual A‐ and B‐site‐deficient cubic perovskite polymorph of Ba8 NiTa6 O24 below 1350°C as an intermediate phase prior to transforming into the hexagonal phase. This cubic polymorph contains 3% A‐site and 9.5% B‐site vacancies plus 3% Ba cations in the B sites and demonstrated remarkable stability below 1350°C when without presence of the molten salt. The cubic polymorph displayed larger ε 36 and τf 110 ppm/°C than the hexagonal polymorph from the MSS (ε 29 and τf 67 ppm/°C). The hexagonal SSS‐processed ceramics showed advantageous dielectric properties ( Qf 52 000 GHz, τf 30 ppm/°C) over both cubic and hexagonal MSS‐processed ones ( Qf 18 600–20 000 GHz), while displaying anisotropic grain growth. The anisotropic grain growth was suppressed significantly by the MSS processing.